If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -7a + -2n + -8 = 0 Reorder the terms: 6 + -8 + -7a + -2n = 0 Combine like terms: 6 + -8 = -2 -2 + -7a + -2n = 0 Solving -2 + -7a + -2n = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -7a + 2 + -2n = 0 + 2 Reorder the terms: -2 + 2 + -7a + -2n = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -7a + -2n = 0 + 2 -7a + -2n = 0 + 2 Combine like terms: 0 + 2 = 2 -7a + -2n = 2 Add '2n' to each side of the equation. -7a + -2n + 2n = 2 + 2n Combine like terms: -2n + 2n = 0 -7a + 0 = 2 + 2n -7a = 2 + 2n Divide each side by '-7'. a = -0.2857142857 + -0.2857142857n Simplifying a = -0.2857142857 + -0.2857142857n
| 11h+6= | | ln(3)+ln(9)=x | | 0.7x+0.4=-1 | | 4(4x+2)+5=16x+13 | | 2x=4(1.50) | | 3(x-4)+3(x-2)=0 | | -9y-3=3 | | 56=8xp | | 9x+4y=172 | | 7k+3-6k=-35 | | X+2*2=3x-8 | | -5x-4y=1 | | b+20+7b=50 | | -.5+a=.625 | | 9(x-9.9)=6.3 | | X+2+x+2=3x-8 | | 2(w-3)=1-(v+4) | | 6(3)-3y=18 | | 10(v-5)+4=11(4+5v) | | e^2x-3=10 | | 6(1)-3y=18 | | X-4+3-2x=4x+5-2x | | 4k^2+11k-15=0 | | an=-4n+-7 | | 9d+15=-15 | | 49-14=7-x | | x(2x-1)=2x(2x)+5x-12 | | 2.8x-43=1.3x+2 | | 5x-6=5x-1 | | X+19+x+19=x+29 | | -.15=.40+0.125p | | -9-4+2M=-9-7M+5 |